Biomechanical and Physiological Evaluation of Biologically-Inspired Hip Assistance With Belt-Type Soft Exosuits - Qiang Chen; Shijie Guo; Jing Wang; Jiaxin Wang; Dan Zhang; Shanhai Jin (IEEE Transactions on Neural Systems and Rehabilitation Engineering, 2022)
Hip-assisted soft exosuits have been reported for their effect on reducing the metabolic power of human walking. Currently, most studies focus on uni-directional assistance (HF: hip flexion, or HE: hip extension). This paper investigates the effect of bi-directional assistance (HFE: hip flexion and extension) on the biomechanics and physiology of the wearer for understanding the potential benefits in synergistic effect of multi-muscle assistance. A belt-type soft exosuit was developed to provide the bi-directional assistance for augmenting walking. The assistance strategy was presented by imitating the contraction mechanisms of hip flexor and extensor muscles in walking. Tests on 8 healthy subjects were conducted and the results were compared with traditional uni-directional assistance. Metabolic powers, muscle activities, kinematics, and kinetics were measured and analyzed. Results showed that HFE assistance reduced the metabolic power by 7% and 12.4% relative to no exosuit and assistance turned off, respectively, larger than the sum of HF and HE. Furthermore, HFE reduced more total joint positive biological work and the activity of more related muscles, and at the same time increased upward and downward accelerations of body mass center, promoting walking energy exchange. These findings demonstrate that bi-directional assistance by combining hip flexion and extension has a significant synergistic effect on augmenting human walking as well as a benefit of increasing biological efficiency.